Effective teaching strategies and inclusive education practices: A case study in Andalucia Prácticas educativas eficaces ante la exclusión educativa Estratégias efetivas de ensino e práticas de educação inclusiva: Um estudo de caso na Andaluzia - José Maria Fernández Batanero (Arizona State University, 2010)
This paper shows the results obtained regarding the educational practices carried out at a high school, catalogued as a center of preferential educational intervention by the Andalusian Educational Administration. The focus of attention is on the students at risk of scholar exclusion, and therefore of dropping out. The methodological design for the investigation, of descriptive nature, has been that of a case study, with three sources of information: documentary analysis, classroom observations, and the perceptions of the persons in charge of implementing the attention to diversity measures. Among the conclusions from the study about prevention of early dropouts, it is worth mentioning, on the one hand, the importance of carrying out planning, organization and teaching strategies with regard to scholar inclusion. On the other hand, the necessity of bringing out new types of coexistence based on respect, as well as developing educational policies that help to encourage a higher level of social commitment, and a better professional development for teachers. Este trabajo presenta  los resultados obtenidos en relación a las prácticas educativas que se desarrollan en un centro de educación secundaria, catalogado por la Administración Educativa Andaluza como centro de actuación educativa preferente. El foco de atención se centra en el alumnado en riesgo de exclusión educativa, y por consiguiente de fracaso escolar. El diseño metodológico de investigación, de carácter descriptivo, ha sido el estudio de caso, con tres principales fuentes de información: el análisis documental, observaciones de aula y las percepciones de los actores responsables de implementar las medidas de atención a la diversidad. Entre las conclusiones del estudio sobre la prevención del abandono temprano destacan, por un lado, la importancia de desarrollar estrategias de planificación, organización y enseñanza acordes con la inclusión educativa. Y por otro, la necesidad de construir nuevos modelos de convivencia basados en el respeto, así como desarrollar políticas educativas que contribuyan a fomentar una mayor implicación social y un mejor desarrollo profesional de los docentes.  Este trabalho apresenta os resultados obtidos em relação às práticas educativas que são desenvolvidas numa escola secundária. Resultados estes, apresentados pela Administração Educacional Andaluza, considerada como centro de referência de actividades de ensino. O foco da atenção está voltado para os alunos em risco de exclusão educacional e, portanto, em risco de fracasso escolar. A metodologia de pesquisa descritiva, foi o estudo de caso, três fontes principais: análise documental, observação de aulas e as percepções dos atores responsáveis pela execução das medidas de atenção à diversidade. Entre as conclusões do estudo sobre a prevenção do abandono precoce incluem-se, em primeiro lugar, a importância de desenvolver estratégias para a planificação, organização e métodos de ensino compatíveis com a inclusão educacional. E em segundo lugar, a necessidade de construir novos modelos de convivência baseada no respeito e desenvolver políticas educacionais para ajudar a promover uma maior participação social e um melhor desenvolvimento profissional dos professores.